Effect of Aortic Valve Disease on Three-Dimensional Hemodynamics in Patients with Aortic Dilation and Trileaflet Aortic Valve Morphology - Suwa, Kenichiro (J Magn Reson Imaging, 2019)
BACKGROUND: The effect of different expressions of aortic valve disease on three dimensional (3D) aortic hemodynamics is unclear. PURPOSE: To investigate changes in aortic hemodynamics in patients with dilated ascending aorta (AAo) but different severity of aortic valve stenosis (AS) and/or regurgitation (AR). STUDY TYPE: Retrospective. POPULATION: A total of 111 subjects (86 patients with AAo diameter ≥40 mm and 25 healthy controls, all with trileaflet aortic valve (TAV)). Patients were further stratified by TAV dysfunction: n=9 with combined moderate or severe AS and AR (ASR, 56±13 years), n=14 with moderate or severe AS (AS, 64±14 years), n=33 with moderate or severe AR (AR, 62±14 years), n=30 with neither AS nor AR (no AS/AR, 63±9 years). FIELD STRENGTH/SEQUENCE: 4D flow MRI on 1.5/3T systems for the in-vivo analysis of aortic blood flow dynamics. ASSESSMENT: Data analysis included grading of 3D AAo vortex/helix flow and AAo flow eccentricity as well as quantification of systolic peak velocities and wall shear stress (WSS). STATISTICAL TESTS: Continuous variables were compared by one-way analysis of variance or Kruskal-Wallis, followed by pair-wise Tukey or Dunn test if there was significant difference. RESULTS: All patients demonstrated markedly elevated vortex and helix flow compared to controls (p<0.05). Peak velocities were significantly elevated in ASR, AS and AR patients compared to controls (p<0.05). Increased flow eccentricity was observed in entire AAo for AR, at the mid and distal AAo for ASR and AS, and at the proximal AAo for no AS/AR. Compared to controls, WSS in the AAo was significantly elevated in ASR and AS patients (p<0.05) and reduced in no AS/AR patients (p<0.05). DATA CONCLUSIONS: The presence of TAV dysfunction is associated with aberrant hemodynamics and altered WSS which may play a role in the development of aortopathy.